Diet and prostate cancer: results from the South and East China—case–control study on prostate cancer. Issue 2 (2013) - Verboom, CE; Zhong, Z; Xie, LP; Hu, Z; Zhong, WD; Wong, YC; Tam, PC; Cheng, KK; Deng, Y; Mao, QQ; Su, Y; Bi, X; et al.
No abstract available